Cdc42 localized in the CatSper signaling complex regulates cAMP‐dependent pathways in mouse sperm - Luque, Guillermina Maria (2021)
Sperm acquire the ability to fertilize in a process called capacitation and undergo hyperactivation, a change in the motility pattern, which depends on Ca2+ transport by CatSper channels. CatSper is essential for fertilization and it is subjected to a complex regulation that is not fully understood. Here, we report that similar to CatSper, Cdc42 distribution in the principal piece is confined to four linear domains and this localization is disrupted in CatSper1-null sperm. Cdc42 inhibition impaired CatSper activity and other Ca2+-dependent downstream events resulting in a severe compromise of the sperm fertilizing potential. We also demonstrate that Cdc42 is essential for CatSper function by modulating cAMP production by soluble adenylate cyclase (sAC), providing a new regulatory mechanism for the stimulation of CatSper by the cAMP-dependent pathway. These results reveal a broad mechanistic insight into the regulation of Ca2+ in mammalian sperm, a matter of critical importance in male infertility as well as in contraception.